The Role of Decision‐Making Models and Reflection in Navigating Ethical Dilemmas. Issue 1 (8th April 2020) - Burkholder, Jessica; Burkholder, David; Gavin, Martin
Abstract : The ACA Code of Ethics (American Counseling Association [ACA], 2014) mandates counselor competency in using ethical decision‐making models (EDMs) and mandates that counselors use an EDM when confronted with making ethical decisions. Additionally, researchers have highlighted the importance of counselors continually evaluating and reflecting when faced with ethical dilemmas and working through a decision‐making model. Using a phenomenological research design, the authors examined how counselors address ethical dilemmas, including how reflection and EDMs are incorporated into the decision‐making process. Emergent themes from data analysis include (a) incomplete following of EDMs, (b) varied dilemmas, (c) power, and (d) ethics training.